A novel tetraethylenepentamine functionalized polymeric adsorbent for enhanced removal and selective recovery of heavy metal ions from saline solutions1. Issue 93 (11th October 2015) - Zhang, Xiao-Peng; Liu, Fu-Qiang; Zhu, Chang-Qing; Xu, Chao; Chen, Da; Wei, Meng-Meng; Liu, Jian; Li, Cheng-Hui; Ling, Chen; Li, Ai-Min; You, Xiao-Zeng
<x xml:space="preserve">Abstract</x> A novel tetraethylenepentamine functionalized polymeric adsorbent with polymethacrylate–divinylbenzene as the substrate was facilely prepared for the enhanced removal and selective recovery of Cu(ii) and Ni(ii) from saline solutions.